Expanding the Functionality of an Autoinduction Device for Repression of Gene Expression in Bacillus subtilis - Silva, Bruna F. [UNESP]; Corrêa, Graciely G. [UNESP]; Zocca, Vitória F. B. [UNESP]; Picheli, Flavio P. [UNESP]; Lins, Milca R. C. R.; Pedrolli, Danielle B. [UNESP] (MDPI, 2023)
Autonomous control of gene expression through engineered quorum-sensing processes is broadly applicable to biosynthetic pathways, including simultaneous control of different genes. It is also a powerful tool for balancing growth and production. We had previously engineered a modular autoinduction device for the control of gene expression in B. subtilis. Now, we expand its functionality to repress gene expression autonomously. The engineered R8 promoter responds to AHL accumulation in the culture medium. In a riboflavin-producing strain, the AHL-Lux complex exerts 5-fold repression on the R8-driven expression of the flavokinase/FAD synthetase gene ribC, resulting in a higher titer of the vitamin. We engineered a strain able to autonomously induce and repress different genes simultaneously, demonstrating the potential of the device for use in metabolic engineering.
Keywords: autoinduction; autonomous control; Bacillus subtilis; dynamic regulation; quorum-sensing; riboflavin